Keterkaitan antara Metode dan Media Pembelajaran IPS terhadap Hasil Belajar Peserta Didik di SDN 55/I Sridadi - Hia, Alice Felicia Azaria; Anggraini, Luvita; Ummah, Ullyl Khoyrul; Sofwan, Muhammad; Noviyanti, Silvina (TSAQOFAH, 2024)
This research aims to determine and analyze the use of learning methods and techniques to improve student learning outcomes at school, improving academic achievement or student learning outcomes as the main goal of the learning process at school. This research uses a mixed type of research (quantitative and qualitative) through descriptive analysis and inferential analysis. The research was carried out at SDN 55/I Sridadi, for research purposes the data collection tool used a questionnaire, research data was analyzed using descriptive analysis and correlation analysis, from this research, in this research it was found that learning methods, media and student learning outcomes were at an average level and there is a close relationship between learning methods and media on student learning outcomes, so it can be said that student learning outcomes can be improved by using good and appropriate learning methods and tools by teachers in the learning process at school.